Mitigating Terminal Heat Stress in Wheat - Suryavanshi, Priyanka; Singh Buttar, Gurmeet (International Journal of Bio-resource and Stress Management, 2023)
Increasing severity of high temperature worldwide presents an alarming threat to wheat in India as late planting of wheat is very common due to the wide spread intensive rice-wheat cropping system particularly in north-west India. As a result, wheat crop has to face the problem of terminal heat stress. It causes a series of morpho-anatomical, physiological and biochemical changes, which affect plant growth and development and results in reduced yield. However, there are various strategies for yield improvement under high temperature stress after anthesis in wheat. Recently, emphasis has been placed on exploiting prompt and inexpensive means of obtaining satisfactory yields from heat stressed lands. One of the pragmatic approaches is the exogenous use of stress alleviating compounds either as seed or foliar application. In this respect, many nitrogenous compounds, inorganic salts, natural and synthetic plant growth regulators and stress signaling molecules have been used based on their specific properties and roles to improve photosynthesis and other physiological functions in wheat. Several osmoprotectants have been reported for alleviating abiotic stresses in wheat. In this literature review, there is an emphasis on the adverse effect of heat stress during reproductive stage of wheat and efficacy of different bio-regulators on grain yield and quality. It also investigates recent advances in research on all these aspects and focuses on osmoprotectants as an effective tool to improve terminal heat tolerance in wheat.